The enhanced rate performance of LiFe0.5Mn0.5PO4/C cathode material via synergistic strategies of surfactant-assisted solid state method and carbon coating. Issue 3 (25th November 2014) - Zhou, Xue; Xie, Ye; Deng, Yuanfu; Qin, Xusong; Chen, Guohua
Abstract : A high rate and cycle performance LiFe0.5 Mn0.5 PO4 /C material was obtained by synergies of a surfactant-assisted solid state method and carbon content. Abstract : The rate performance of LiMnPO4 -based materials is further improved via synergistic strategies including a surfactant-assisted solid state method, Fe-substitution and carbon-coating. The surfactant-assisted solid state strategy effectively decreases the primary particle size of the cathode material, which can greatly shorten the diffusion distance of lithium ions. The Fe-substitution improves the effectiveness of Li + insertion/extraction reactions in the solid phase. The uniform carbon coating layer and the conductive networks provided by the carbon between the nanoparticles ensure the continuous conductivity by the nanoparticles. As a consequence of the synergistic effects, the as prepared LiFe0.5 Mn0.5 PO4 sample with 6.10 wt% carbon exhibits high specific capacities and superior rate performance with discharge capacities of 155.0, 140.9 and 121 mA h g −1 at 0.1, 1 and 5 C (1 C = 170 mA g −1 ), respectively. Meanwhile, it shows stable cycling stability at both room temperature (25 °C, 94.8% and 90.8% capacity retention after 500 cycles at 1 and 5 C rates, respectively) and elevated temperature (55 °C, 89.2% capacity retention after 300 cycles at 5 C rate). This material may have great potential application in advanced Li-ion batteries.